Mycorrhizae and Biofertilizers Applications Stimulate Pineapple Growth in Acidic Soil - Fitriyani, Indri Hapsari; Santosa, Dwi Andreas; Hazrah, Fahrizal; Nurfadila, Uci; Falih, Fairuz Annabil (Department of Agronomy and Horticulture, IPB University, 2025)
Pineapple is a leading commodity worldwide and can grow in a variety of mineral and organic soils. Excessive use of inorganic fertilizers has a detrimental impact on soil and crop health. Biofertilizers contain beneficial microorganisms that can enhance soil fertility, improve soil health, and promote sustainable crop production. This study aimed to investigate the crucial role of biofertilizers and mycorrhizae in promoting the vegetative growth of pineapple in acidic soils. The experiment was conducted using a completely randomized design with nine treatment levels and five replications. The results showed that the mycorrhizae applied at 5 g per plant, combined with full doses of chemical fertilizer (0.5 g ZA, 2 g DAP, and 2 g KCl per plant), produced the highest mycorrhizal colonization in treatment P4. Meanwhile, Provibio® biofertilizer at 5 mL per plant (diluted in 0.5 L water), mycorrhizae at 2.5 g per plant, and half doses of chemical fertilizer (0.25 g ZA, 1 g DAP, and 1 g KCl per plant (P8), improved vegetative growth and soil properties (pH, organic C, and total N) and supported the highest microbial population in the rhizosphere (26.05 × 10⁴ CFU.g-1 soil). This study demonstrated that the combined application of biofertilizers and mycorrhizae in moderate doses is more effective than full single-dose applications, leading to healthier soils and stronger vegetative growth of pineapple in acidic soils.